Reducing the carbon footprint of railway sleepers using recycled plastics - Luomala, Heikki; Halme, Rami; Jönkkäri, Ilari (Frontiers in Sustainability, 2024)
The primary contributors to greenhouse gas (GHG) emissions in railway transport include the energy consumed during transportation, the materials used for infrastructure construction, and maintenance. Track structures commonly employ materials with a substantial carbon footprint, such as concrete and steel. This article explores the feasibility of using materials with a smaller carbon footprint for track structures. Recycled plastics that are currently incinerated might serve as a viable alternative.The key research question revolves around whether GHG emissions resulting from track construction and maintenance can be reduced by utilizing recycled plastics. Among various track components, sleepers were chosen as a potential application for recycled plastic due to their substantial material usage and consequent impact on overall emissions. The study also investigated the necessary material properties for plastic sleepers and assessed whether recycled plastic could meet those requirements. The study investigated recycled plastic fractions, including waste materials recycled by incineration, acrylonitrile butadiene styrene (ABS) from waste electrical and electronic equipment (WEEE), and a byproduct of liquid packaging cardboard repulping (LPB repulping reject). These materials offer a reduced carbon footprint because they have already completed one life cycle and can still be recycled as material. To assess their mechanical properties, laboratory tests were conducted on injectionmolded test rods made from recycled plastic components. These rods underwent tensile and bending tests using a universal testing device. Additionally, the softening temperatures of the materials were measured through Vicat and HDT tests. Finally, based on the amount of waste material flows, the emission reduction potential obtained using recycled plastic was evaluated. Recycled ABS is significantly more suitable for use in track structures due to its superior mechanical durability compared to LPB repulping reject. Additionally, recycling ABS as a sleeper material significantly reduces overall GHG emissions compared to incineration.